Darobactins Exhibiting Superior Antibiotic Activity by Cryo‐EM Structure Guided Biosynthetic Engineering. Issue 2 (7th December 2022) - Seyfert, Carsten E.; Porten, Christoph; Yuan, Biao; Deckarm, Selina; Panter, Fabian; Bader, Chantal D.; Coetzee, Janetta; Deschner, Felix; Tehrani, Kamaleddin H. M. E.; Higgins, Paul G.; Seifert, Harald; Marlovits, Thomas C.; et al.
Abstract: Over recent decades, the pipeline of antibiotics acting against Gram‐negative bacteria is running dry, as most discovered candidate antibiotics suffer from insufficient potency, pharmacokinetic properties, or toxicity. The darobactins, a promising new small peptide class of drug candidates, bind to novel antibiotic target BamA, an outer membrane protein. Previously, we reported that biosynthetic engineering in a heterologous host generated novel darobactins with enhanced antibacterial activity. Here we utilize an optimized purification method and present cryo‐EM structures of the Bam complex with darobactin 9 (D9), which served as a blueprint for the biotechnological generation of twenty new darobactins including halogenated analogs. The newly engineered darobactin 22 binds more tightly to BamA and outperforms the favorable activity profile of D9 against clinically relevant pathogens such as carbapenem‐resistant Acinetobacter baumannii up to 32‐fold, without observing toxic effects. Abstract : Structural evaluation of the Bam complex with darobactin 9 using cryo‐EM combined with bioactivity evaluation led to biosynthetic engineering of novel derivatives with enhanced activity against Gram‐negative pathogens, including clinically relevant isolates. The currently most promising derivative darobactin 22 verified the structure and activity guided approach, exhibiting up to 128‐fold increased activity compared to natural darobactin A.